Studies of Cross-Reactivity of Acquired Factor VIII Inhibitor Activity in Hemophilic Plasma - Abildgaard, C. F; Vanderheiden, J; Lindley, A; Rickles, F (Thrombosis and Haemostasis, 1967)
The plasma of a hemophilic patient with acquired factor VIII inhibitory activity was found to be time and temperature dependent, resistant to heat and stable on storage at -20°. Studies revealed cross-reactivitiy with 11 different mammalian plasmas but no cross-reaction was found with chicken plasma. The inhibitory activity of the plasma studied was neutralized by fresh normal plasma and normal serum but not by aged normal plasma or hemophilic plasma (20 patients). Comparison of the present findings with other reports suggest a difference in cross-reactivity of acquired inhibitors and inhibitory activity induced by immunization of animals.